HUBUNGAN UMUR DAN PARITAS IBU BERSALIN DENGAN KEJADIAN LASERASI DI RUMAH SAKIT PUSRI PALEMBANG TAHUN 2017 - Rosmiarti Rosmiarti; Suci Lestari (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2018)
The purpose of this study was to monitor vital signs, to evaluate the origin of bleeding, and to estimate the number of advanced bleeding and to assess muscle tone at palembang pusri hospital by 2017. This research uses analytical survey method using Cross Sectional approach. The sample of this research is taken by Random Sampling.The results of the authors were the distribution of the laceration frequency of births from 285 respondents as much as 16.6 people (556.6%) of the lacerations and those that did not and no laceration was 123 (43.0%). Age as many as 123 (61.8%) who are at risk and not at risk as much as 162 (37.8%). The parity of Pusri Palembang Hospital in 2017 from 285 respondents was 177 (61.9%) with high risk parity and low risk parity of 108 (37.9%). There was no correlation between maternal age and the incidence of laceration of birth canal with chi-square value obtained on education variable p value = 0.000 < 0.05. In the age variable p value = 0.000a < 0.05. On the parity variable p value = 0.000a < 0.05.astatistically, there was no relationship between age and parity with the incidence of laceration of the birth canal